Abnormal expression of circRNA_089763 in the plasma exosomes of patients with post‑operative cognitive dysfunction after coronary artery bypass grafting - Wang, Maozhou; Su, Pixiong; Liu, Yan; Zhang, Xitao; Yan, Jun; An, Xiangguang; Wang, Xiaobin; Gu, Song (Molecular medicine reports, 2019)
Post‑operative cognitive dysfunction (POCD) is a complication of the central nervous system characterized by mental disorders, anxiety, personality changes and impaired memory. POCD occurs frequently after coronary artery bypass grafting (CABG) and can severely affect quality of life for patients. To date, the development of POCD biomarkers remains a challenge. Alterations in the expression of non‑coding RNAs from brain tissue and peripheral blood have been linked to POCD. The present study aimed to detect the differential circular RNAs (circRNAs) in plasma exosomes of patients with POCD after CABG. The relative expression levels of circRNAs were analyzed using circRNA microarray analysis in the plasma exosomes of patients with POCD. Differentially altered circRNAs (P<0.05, fold change >1.5) were validated by reverse transcription‑quantitative PCR in the plasma exosomes of patients with POCD. The target genes of the microRNAs were predicted using bioinformatics analysis. The functions and signaling pathways of these target genes were investigated by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes analyses. The microarray results indicated that the levels of nine circRNAs in patients with POCD were higher than those in the control subjects; and six circRNAs were at a lower level than those in control subjects. The RT‑qPCR results from patients with POCD showed that only circRNA_089763 of the 15 circRNAs identified was significantly increased compared with control subjects. circRNA target gene prediction and functional annotation analysis showed significant enrichment in several GO terms and pathways associated with POCD. The present study provides evidence for the abnormal expression of POCD‑induced circRNA_089763 in human plasma exosomes, as well as the involvement of POCD.